The role of lexical morphology in the recognition, Spain - Lázaro Lópe.Villaseñor, Miguel (2010)
In the lexicon there are stored and processed a huge number of words. Taking into account the limited capacities of the brain, it is only possible this store because of the economical structure of the lexicon. On the research of the lexical structure stands out from three decades the study of the role played by morphology. A number of investigations, with and without brain damaged subjects, have shown that morphology plays an important role on the lexical access, although its role is still not very well know. In this study we make a deep revision of the main researches concerning the role of morphology, and discuss the results on the light of the different models proposed.